Pengembangan sistem informasi geografis untuk pemetaan bangunan gedung pemerintah di kota Bandung - Hafsah Islamiati Ayuningtyas; Wahyu Purnama Sari; Bintang Bahari; Triansyah Amarullah Ahmad Prayoga; Prawira Setia Ramdhani (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
Advancements in information technology have created significant opportunities for more efficient spatial data management, including the mapping of government buildings. To support this effort, this study develops a web-based geographic information system for mapping government buildings in Bandung City using Leaflet.js. The system aims to facilitate interactive map visualization and provide more accurate and structured access to spatial data. The Agile method is applied in the system development process, consisting of six main stages: needs identification, design, development, testing, implementation, and evaluation. The system is designed using the Laravel or CodeIgniter framework as the backend and Leaflet.js for dynamic spatial data presentation. The research results indicate that the system can display geographic information accurately and interactively while supporting search, filtering, and responsive map display features across various devices. Additionally, the Agile approach has proven to enhance development efficiency and user experience. With this system, the government can manage building data more effectively, transparently, and efficiently to support planning and decision-making based on spatial data.